2020
DOI: 10.1021/acs.langmuir.9b03892
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Responsive Poly(N-Isopropylacrylamide) Nanogels: The Role of Hollow Cavities and Different Shell Cross-Linking Densities on Doxorubicin Loading and Release

Abstract: Smart polymers with extraordinary characteristics are studied in drug-delivery applications. In the current study, temperature-responsive hybrid core−shell nanoparticles were synthesized by precipitation polymerization of N-isopropylacrylamide and vinyl-modified silica nanoparticles. These temperature-responsive hybrid core−shells were prepared with different cross-linking densities by using 2, 4, and 8 mol % of N,N-methylene bisacrylamide (MBA). Hydrolysis of the silica cores of the hybrid core−shells resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 72 publications
(106 reference statements)
0
47
0
Order By: Relevance
“…For example, Luckanagul reported the synthesis of chitosan-based nanogels with modification by thermo-sensitive PNIPAM and CUR was successfully loaded through a simple sonication method in aqueous media, showing temperature-responsive drug release behaviors (Luckanagul et al, 2018b). In order to study the influence of the degree of crosslinking and the existence of holes in the nanogels on the drug loading and release characteristics, Hajebi synthesized temperature-responsive hybrid core-shell nanogels using NIPAM and vinyl-modified silica nanoparticles via precipitation polymerization, and hollow PNIPAM nanogels were obtained by hydrolysis of silicic acid (Hajebi et al, 2020). All results demonstrated that the hollow nanogels had higher DOX loading content and higher toxicity, whereas hybrid nanogels showed faster drug release.…”
Section: Temperature-sensitive Nanogelsmentioning
confidence: 99%
“…For example, Luckanagul reported the synthesis of chitosan-based nanogels with modification by thermo-sensitive PNIPAM and CUR was successfully loaded through a simple sonication method in aqueous media, showing temperature-responsive drug release behaviors (Luckanagul et al, 2018b). In order to study the influence of the degree of crosslinking and the existence of holes in the nanogels on the drug loading and release characteristics, Hajebi synthesized temperature-responsive hybrid core-shell nanogels using NIPAM and vinyl-modified silica nanoparticles via precipitation polymerization, and hollow PNIPAM nanogels were obtained by hydrolysis of silicic acid (Hajebi et al, 2020). All results demonstrated that the hollow nanogels had higher DOX loading content and higher toxicity, whereas hybrid nanogels showed faster drug release.…”
Section: Temperature-sensitive Nanogelsmentioning
confidence: 99%
“…Regarding the use of microgels as drug-delivery vehicles, many different studies have been performed with varying drugs, ranging from lysozyme [ 24 ] over the more hydrophilic drugs dopamine, naproxen, desipramine, dibucaine, acetaminophen [ 25 ], and -aescin [ 26 ] to the hydrophobic doxorubicin (DOX) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Just from these representative examples, it can be stated that the structure of microgels, which often exhibit a rather hydrophobic, cross-linker rich core region and a rather hydrophilic corona [ 34 ], enables these particles to act as carriers for a variety of hydrophilic and hydrophobic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst, "smart" chemotherapy using stimuli-responsive hydrogels based on natural polymers have received more interest owing to intrinsic physicochemical and biological properties of these drug delivery systems (DDSs). [5][6][7][8][9] Amongst the variety of natural polymers, gelatin (Gel) as a thermo-sensitive natural polypeptide is widely used for the fabrication of de novo DDSs. It isolated from animal collagen through partial acidic (type A), alkaline (type B), or enzymatic hydrolysis that can be utilize in pharmaceutical technology as hard or soft capsules.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the specific advantages of above‐mentioned approaches, off‐targeting of their have been challenged in most cases. Amongst, “smart” chemotherapy using stimuli‐responsive hydrogels based on natural polymers have received more interest owing to intrinsic physicochemical and biological properties of these drug delivery systems (DDSs) 5–9 …”
Section: Introductionmentioning
confidence: 99%